Prinsip Kerja Sama dalam Berinteraksi di Lingkungan SMPN 11 Kota Jambi - Hendri Ristiawan (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2017)
ABTRACT The results of this research can be obtained some maxim of cooperation principle, that is maxim of quantity, maxim of quality, maxim of relationship and maxim of behavior. Also obtained some violations of the principle of cooperation. both violation of quantity of maxim, maxim of quality, maxim of relationship and maxim of behavior in interaction in SMPN 11 environment. Keywords: the violating of cooperation principle, maxim